A Cultural-Historical Construction of Safety Education Programs for Preschool Children: Findings from SeeMore Safety, the Pilot Study. Issue 2 (June 2013) - O'Neill, Susie; Fleer, Marilyn; Agbenyega, Joseph; Ozanne-Smith, Joan; Urlichs, Megan
SCIENTIFIC RESEARCH HAS BEEN dealing with the problem and prevention of unintentional injury in children for some time, yet injury rates continue to increase in some areas. This paper reports on the outcomes of a study of children from seven preschools in a rural region of Australia, who were engaged in a cultural-historically designed safety education program. The study sought to examine the relations between safety knowledge and perceived action gained as a result of participation in a program called 'SeeMore Safety'. SeeMore Safety combines preschool and home-based education for children aged four to six years, their parents and teachers. Using a mixed-method research approach, the study examined how the program contributed to knowledge of injury prevention in young children. The findings demonstrated that it had a positive effect on preschool children's behaviour and reasoning about safety. The paper concludes with an argument about the need for further research into this important area of early childhood education.